Lean Six Sigma implementation in the food sector: nexus between readiness-critical success factors - Abdul Halim Lim, Sarina; Azalanzazllay, Nurul Najihah; Priyono, Anjar; Inan, Guven Gurkan; Hussain, Muhammad Iqbal (Advances in Science, Technology and Engineering Systems Journal, 2021)
Lean Six Sigma (LSS) is a renowned approach for boosting operational excellence and competitive advantage through integrated core objectives of value creation and variation reduction. Despite its proven benefits in many leading companies, LSS implementation in the food sector is still behind compared with other sectors. LSS implementation is costly, and most businesses have failed due to a lack of preparation and an unsupportive organizational culture. Therefore, there is a need to identify LSS readiness factors that suit the food sector to minimize the risk of implementation failure in the industry. The current study concentrates on the LSS pre-implementation phase to determine the competency criteria to adopt LSS customized for the food business. This study will explore the LSS readiness criteria during the pre-implementation stage and critical success factors (CSFs) during the implementation stage in the food sector through Lewin’s Change Theory. Twelve food sector employees who were associated with quality management activities were interviewed using a semi-structured approach. The interview was recorded, transcribed and the transcription was analyzed using content analysis. The results showed six readiness themes in the food manufacturing sector with twenty-nine LSS readiness attributes, while seventeen factors out of thirty-one CSFs for the LSS at the implementation stage. The identified readiness factors are management commitment and leadership (ten attributes), organizational culture (nine attributes), employee involvement (six attributes), process management (four attributes), project management (four attributes) and external factors (three attributes). Through Pareto analysis, the most prioritized CSFs are from top management and leadership and employee involvement themes, with the training program being identified as the most important LSS CSFs (85%). This study will serve as a foundation for a benchmarking tool for managers to improve the effectiveness of an LSS implementation in the food sector.